Employee Work Productivity Is Influenced by Motivation and Work Discipline: Case Study On Employees Of PT Dirgantara Indonesia Main Directorate Area - Fahmanagari, Rina Adysholihah; Firmansyah, Yayan; Joeliaty, Joeliaty (Jurnal Computech & Bisnis (e-journal), 2024)
PT Dirgantara Indonesia is a large company in the manufacturing industry sector. In the last three years, the company has experienced business challenges, namely project declines and 22% delays in completion. The factor that most influences the delay in project completion is work productivity. The decline in employee productivity is influenced by work motivation and discipline. This study aims to determine motivation, work discipline and work productivity and their interrelationships with each other partially and simultaneously on employees of PT Dirgantara Indonesia Main Directorate Area. In this study, data analysis used multiple linear regression analysis with descriptive methods. The sample was taken using a saturated sample, which used all members of the population as a sample of 117 people. The results of the study show that motivation, work discipline and work productivity of employees are included in the sufficient category. In addition, work motivation and discipline partially and simultaneously have a positive effect on work productivity with a contribution value of work motivation and discipline of 42.1% and the remaining 57.9% is influenced by other variables not used in this study.